2020
DOI: 10.3390/app10175989
|View full text |Cite
|
Sign up to set email alerts
|

MERLIN a Cognitive Architecture for Service Robots

Abstract: Many social robots deployed in public spaces hide hybrid cognitive architectures for dealing with daily tasks. Mostly, two main blocks sustain these hybrid architectures for robot behavior generation: deliberative and behavioral-based mechanisms. Robot Operating System offers different solutions for implementing these blocks, however, some issues arise when both are released in the robot. This paper presents a software engineering approach for normalizing the process of integrating them and presenting them as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Recent works such as [1], [5], [10] and [12] have successfully incorporated LLMs and VLMs into robotic systems, allowing the LLMs to interpret and execute complex commands. Similarly, Wangchunshu et al [35], Kaiwen Zhou et al [34], and Miguel et al [9] in their work demonstrated how LLMs could be used to facilitate real-time feedback, zero-shot object navigation and cognitive learning in autonomous robots.…”
Section: Related Workmentioning
confidence: 99%
“…Recent works such as [1], [5], [10] and [12] have successfully incorporated LLMs and VLMs into robotic systems, allowing the LLMs to interpret and execute complex commands. Similarly, Wangchunshu et al [35], Kaiwen Zhou et al [34], and Miguel et al [9] in their work demonstrated how LLMs could be used to facilitate real-time feedback, zero-shot object navigation and cognitive learning in autonomous robots.…”
Section: Related Workmentioning
confidence: 99%
“…This research uses MERLIN [ 58 ], which combines deliberative and behavioural capacities. Deliberative capacities define the characteristics of planning to infer long-term tasks.…”
Section: System Architecturementioning
confidence: 99%
“…It assumes a background approach, feeding a knowledge database and keeping the deliberative monitoring system that would interrupt the active task up to date. The architecture proposed in [ 58 ] requires to be updated by including the new vision-based module proposed in this paper in the reactive layer. As this reactive layer gathers all the sensors of the robot, with the proposed vision module, the images acquired by the robot camera are processed.…”
Section: System Architecturementioning
confidence: 99%
“…In [29], researchers developed TRs for offices, healthcare systems, and nursing homes. Another useful application is augmented virtual reality, which is useful to simulate the feeling of a human-robot interactive environment [30][31][32][33]. In [34], immersed virtual reality was developed to provide guidelines for user design.…”
Section: Introductionmentioning
confidence: 99%